PENGARUH PENGGUNAAN SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI DI SMK NEGERI 1 BATANG PERANAP KABUPATEN INDRAGIRI HULU - Rani, Gusti; Nas, Syakdanur; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACK : The objectives of this research were to know the effect of using learning resources that used by accounting student of class X, XI, XII in accounting subject in SMKN 1 Batang Peranap. The population of this research was the class X, XI, XII SMKN 1 Batang Peranap amount 139 people and the sample amount 59 people. The collected data used questionnaire and documentation. Data analysis of this research used simle linier regression. Research result based on simple linier regression showed that the using of learning resources influence on student learning outcomes of class X, XI, XII in accounting subject in SMKN 1 Batang Peranap this can be seen from a constant value (a) of 48,306 and the value coefisien regression (b) of 0,772 with a regresiion equation 48, 306 + 0,772. According the calculation of R (R squer change) obtained a value of 0,553. It means that the contribution of the influence of the use learning resources on learning outcomes by 55,3%.Keyword : Using Learning Outcomes, Learning Outcomes